Regulation of insulin secretion in human pancreatic islets. - Rorsman, P; Braun, M (2013)
Pancreatic β cells secrete insulin, the body's only hormone capable of lowering plasma glucose levels. Impaired or insufficient insulin secretion results in diabetes mellitus. The β cell is electrically excitable; in response to an elevation of glucose, it depolarizes and starts generating action potentials. The electrophysiology of mouse β cells and the cell's role in insulin secretion have been extensively investigated. More recently, similar studies have been performed on human β cells. These studies have revealed numerous and important differences between human and rodent β cells. Here we discuss the properties of human pancreatic β cells: their glucose sensing, the ion channel complement underlying glucose-induced electrical activity that culminates in exocytotic release of insulin, the cellular control of exocytosis, and the modulation of insulin secretion by circulating hormones and locally released neurotransmitters. Finally, we consider the pathophysiology of insulin secretion and the interactions between genetics and environmental factors that may explain the current diabetes epidemic.